Hop biomass waste against fire blight and black rot: an eco-friendly approach to crop protection - Fontana, Riccardo; Leto, Leandra; Ortore, Maria Grazia; Guarrasi, Valeria; Pula, Walter; Esposito, Elisabetta; Bigi, Francesco; Chiancone, Benedetta; Marconi, Peggy (Frontiers in Microbiology, 2025)
Hop is a perennial, deciduous climbing plant best known for its use in beer production. Recently, in line with the Green Strategy of Agenda 2030 and increasing market demand, research and industry interest in natural products has grown. In this context, hop biomass waste (HW), such as leaves, stems and non-standardized cones discarded after cone harvesting, has been shown to contain a wealth of bioactive compounds. These compounds offer promising applications in several productive sectors, including the pesticide industry. This study aims to evaluate the effect of extracts obtained from powdered HW (HWP) on two quarantine phytopathogenic bacteria: Erwinia amylovora (EA), the causal agent of fire blight in Rosaceae, and Xanthomonas campestris pv. campestris (Xcc), the causal agent of black rot in crucifers. Both diseases are highly destructive and economically impactful, necessitating the search for effective and eco-friendly alternatives. Various extracts were prepared, including two hydroalcoholic ones (ethanol/water 80:20 and 70:30), one ethanolic extract, and one methanolic extract. The potential mechanisms of action were investigated, with a focus on bacterial membrane permeability, biofilm formation and removal, and antioxidant activity, assessed using the Folin–Ciocalteu test. The in vitro analyses demonstrated that HWP extracts exhibit significant antibacterial activity against both EA and Xcc by altering bacterial membrane permeability, inhibiting biofilm formation, and promoting biofilm removal. The Folin–Ciocalteu test confirmed the presence of polyphenols, suggesting antioxidant activity. In planta tests provided realistic insights into the interaction between plants, bacteria, and extracts, showing promising results for the use of HWP extracts in controlling these phytopathogens. The study highlights the high efficacy, eco-friendliness, and sustainability of low-cost HWP extracts as a potential strategy for controlling fire blight and black rot. HWP extracts could serve as an alternative to traditional synthetic pesticides and antibiotics, promoting more sustainable and environmentally friendly agricultural practices, in line with Sustainable Development Goal 2 of the 2030 Agenda.